The Blakeney Government and the Settlement of Treaty Indian Land Entitlements in Saskatchewan, 1975-1982 - Pitsula, James (Historical Papers / Communications historiques, 1989)
AbstractBetween 1975 and 1982 a concerted effort was wade to fulfil treaty Indian land entitlements in Saskatchewan. The provincial NDP government led by the Hon. A.E. Blakeney proposed the “Saskatchewan formula” as the basis for a settlement. The process of settling entitlements was a complex one, but a close analysis of the federal-provincial negotiations suggests that most of the responsibility for the lack of progress belongs to the federal government. The flexible approach taken by the Saskatchewan government, who interpreted land entitlements in the context of the “spirit and intent” of the treaties, collided with the relatively inflexible approach of the federal Office of Native Claims, who were wedded to the concept of “lawful obligation.” When the problem was delayed in its solution, various groups had time to mount opposition to the proposed settlement. Consequently, a great opportunity was missed to achieve a major breakthrough and bring about an easing of tensions between Indians and non-Indians in Canada.